Factor Analysis of the Creative Thinking Test - Graphic Production - Мirjana М. Јаpundža-Мilisavljević; Biljana Z. Мilanović-Dobrota (University of Belgrade, Teacher Education Faculty, 2023)
Development of creativity is an important segment of educational process. The goal of this research is to identify the factor structure of the Creative Thinking Test - Graphic Production of the applied on the sample of students with intelectual difficulties. The sample consisted of 76 students, age 9-14 (АS=11,54; SD=1,75), of both genders (53,3% boys and 46,7% girls), without neurological or multiple impediments. The creative potential of these students was tested using the Creative Thinking Test - Graphic Production. By analyzing the obtained resutls we identified two factors which explain the total of 67,6% of the variance. The first factor has four main factor weights (fragment-dependent boundary breaking, fragment-independent boundary breaking, humour, and new elements). The second factor includes linking by drawing lines, continuation, addition, and linking that contributes to the topic. Unconventional material manipulation as well as the use of abstract elements have the least factor weights. The two-factor model showed acceptable suitability indices and suggests the importance of conventional and unconventional ways of thinking for the creative process of students with intellectual difficulties.